2000
DOI: 10.1111/j.1468-5906.2000.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Attaining “a Sophisticated Maturity:” A Brief History of the Journal for the Scientific Study of Religion

Abstract: An historical overview of the Journal for the Scientific Study of Religion considers both the aspirations of the founders and the extent to which those aspirations have been realized, modified, or exceeded. Appropriate secondary sources are reviewed for an understanding of the intellectual and organizational contexts giving rise to the Journal and for a qualitative consideration of its earliest decades. Then we introduce quantitative data derived from tabulations of all articles and research notes that have ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 162 publications
0
7
0
Order By: Relevance
“…Overall, the articles in this review issue tended to express optimism when evaluating the progress made within the discipline, contending that article quality was better, the methodologies used were more complex, and the number of topics studied was more diverse (Maus and Hammons 2000). One exception to this trend was the critical assessment of the field offered by Wallace (2000) in which she discussed her early attempts to "bring women into" the study of religion.…”
Section: Previous Analysis Of the Sociology Of Religionmentioning
confidence: 96%
“…Overall, the articles in this review issue tended to express optimism when evaluating the progress made within the discipline, contending that article quality was better, the methodologies used were more complex, and the number of topics studied was more diverse (Maus and Hammons 2000). One exception to this trend was the critical assessment of the field offered by Wallace (2000) in which she discussed her early attempts to "bring women into" the study of religion.…”
Section: Previous Analysis Of the Sociology Of Religionmentioning
confidence: 96%
“…In an analysis of articles published in JSSR through 1999, Mauss and Hammons (2000) found that 54 percent of authors were sociologists and 21 percent were psychologists. Curious as to my own record for the past three years, I did my own count of the disciplines represented in the 48, 49, and 50th volumes of the journal.…”
mentioning
confidence: 99%
“…The language of their statement (“postulates,”“empirical,”“operational,”“probabilities,”“scientific,”“objectivity”) indicates a keen concern with the application of a positivist framework. The emergence of SSSR was not without conflict as so‐called partisans attempted to push the Society in one direction or another (Mauss and Hammons 2000:450). That same conflict is apparent in a more recently published debate about progress and cumulation of knowledge in the sociology of religion (Chaves 2003): conflicts between professional organizations, between religious and scientific worldviews, between qualitative/interpretive and quantitative/positivist approaches.…”
mentioning
confidence: 99%
“…That issue, Moving Forward by Looking Back: A Half Century of the SSSR, RRA, and Social Scientific Research on Religion (volume 39, issue 4, 2000) focused on the founding and establishment of the scientific study of religion. In that volume, Mauss and Hammons (2000) claimed JSSR had achieved the “sophisticated maturity” envisioned by Pemberton, offering “many a scholar the opportunity to introduce a line of endeavor in its earliest stages, attracting the first public attention to work that would eventually appear in a series of later articles or even in books (463–64).”…”
mentioning
confidence: 99%